Revision of the Genus Crioprosopus Audinet-Serville, and description of three new genera of Trachyderini (Coleoptera: Cerambycidae: Cerambycinae) - Eya, Bryan K. (Zootaxa, 2015)
The genera Callona Waterhouse, 1840 and Crioprosopus Audinet-Serville, 1834 (Coleoptera: Cerambycidae: Cerambycinae: Trachyderini) are revised. The genus Callona is synonymized with Crioprosopus, and new genera, Callistochroma gen. nov., Megapurpuricenus gen. nov. and Pilostenaspis gen. nov. are described. Five species, three previously included in Callona [C. flavofasciata Chemsak & Hovore, 2011, lampros (Bates, 1885), and rutilans (Bates 1869)], and two from Crioprosopus [C. cacicus (Bates, 1885) and viridipennis (Latreille, 1811)], are transferred to Callistochroma, with viridipennis designated as the type species. Two species, one previously described as Crioprosopus (C. lateralis LeConte, 1884) and another from Stenaspis Audinet-Serville (S. pilosella Bates, 1892), are transferred into Pilostenaspis, with lateralis designated as the type species. Crioprosopus magnificus (LeConte, 1875) is transferred into Megapurpuricenus, and designated as the type species. Keys to the above genera and species along with illustrations of the available species in color are included. New species described include: Pilostenaspis copei sp. nov. from Mexico; Crioprosopus wappesi sp. nov. from Guatemala; Crioprosopus hondurensis sp. nov. from Honduras; Callistochroma chrysiptera sp. nov. and Crioprosopus chiriquiensis sp. nov. from Panama, and Callistochroma viridipurpurea sp. nov. from Colombia.